Assessing farmers` knowledge of weed species, crop type and soil management practices in relation to soil quality status in mai-negus catchment, northern Ethiopia - Tesfahunegn, Gebreyesus Brhane; Tamene, Lulseged D.; Vlek, Paul L.G.; Mekonnen, Kindu (Wiley, 2016)
Soil quality (SQ) assessment from farmers' point of view can be used as a primary indicator for planning sustainable agriculture. Despite this fact, limited information is documented with regard to SQ indicators, for example weed species, crop types and management practices from farmers' knowledge perspectives. The aims of this study are to analyse factors that determine farmers' knowledge of SQ, identify SQ indicators of weed species and crop types across different SQ status and assess soil‐and‐crop management practices that maintain SQ in the Mai‐Negus catchment, northern Ethiopia. Fifty‐two farmer household heads were chosen randomly for questionnaire interview. The results showed significant (p ≤ 0·05) differences in the proportion of respondents who used different crop‐and‐soil management practices. The success of overall prediction by the logistic regression model (model χ2 = 0·84, p < 0·01) and level of model correct predictions (86%) indicated that the explanatory variables have sufficiently explained farmers' knowledge of SQ indicators. Provided that other conditions remained constant, the odds ratio of variables such as farmer experience, access to information, farm location, education, field slope and land tenure have significantly increased the likelihood of farmers for being knowledgeable of SQ indicators. This study also demonstrated that most farmers are knowledgeable in identifying weed species, crop types and management practices across various SQ status, which suggests that such SQ indicators should be used to assess SQ status (degradation severity) while locating fields to be intervened using appropriate management strategies. © 2013 The Authors. Land Degradation & Development published by John Wiley & Sons, Ltd.